Construction method and evaluation method of alloy phase boundary / grain boundary irradiation damage behavior model

By constructing an alloy phase/grain boundary irradiation damage behavior model, the damage behavior of magnesium alloy in high irradiation environment is simulated, and the problems of insufficient plastic deformation ability and unclear radiation resistance mechanism of magnesium alloy are solved, and radiation resistance to magnesium alloy is achieved In-depth understanding of performance.

CN119397760AActive Publication Date: 2025-02-07SOUTHWEST JIAOTONG UNIV

Patent Information

Application Number
CN202411442003.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Magnesium alloys have insufficient plastic deformation ability under high irradiation environments, and the resistance mechanism of its grain boundaries and phase boundaries to radiation is unclear.

Method used

A model of damage to the damage of the alloy phase boundary/grain boundary was constructed. Through the first principle calculation method, the grain boundary and phase boundary response of magnesium alloy to irradiation is simulated, and the damage effect of Au ion irradiation on the phase boundary of magnesium alloy was explored.

Benefits of technology

A detailed simulation of the irradiation damage behavior of magnesium alloys was realized, revealing the resistance mechanism of grain boundaries and phase boundaries to radiation, and providing a theoretical basis for improving the irradiation resistance of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119397760A_ABST
    Figure CN119397760A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nuclear engineering, and particularly relates to a construction method and an evaluation method of an alloy phase boundary / grain boundary irradiation damage behavior model, and the method comprises the following steps: obtaining a crystal face and a crystal face included angle of alpha-Mg in AZ31 according to an EBSD result graph of AZ31, obtaining crystal faces and crystal face included angles of (1100) Mg and (200) Li according to a TEM result graph of LZ91, and constructing a phase boundary interface model of alpha-Mg and beta-Li; s2, building a surface model through the crystal face obtained in the step S1, obtaining the number of surface atomic layers, adding a vacuum isolation layer on the surface model, carrying out a convergence test on the surface model, and respectively building interface models of the AZ31 magnesium alloy and the LZ91 magnesium-lithium alloy through obtained results; and S3, an Mg vacancy, a Li vacancy, an Mg vacancy and a Li vacancy are doped in the interface model obtained in the S2, and an alloy phase boundary / grain boundary irradiation damage behavior model is constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nuclear engineering, and in particular relates to a method for constructing and evaluating an alloy phase boundary / grain boundary radiation damage behavior model. Background Art

[0002] As a new type of sustainable clean energy, nuclear power is one of the important pillars of global electricity supply. High-performance reactor structural materials play an important role in the safe and stable operation of nuclear power plants. Magnesium alloys are often used as cladding materials in CO2 gas-cooled reactors when uranium is used as nuclear fuel due to their stability in anhydrous environments and good compatibility with uranium. At the operating temperature of the gas-cooled reactor, magnesium alloys are required to have sufficient plasticity to prevent them from damaging the cladding during the core deformation process. At the same time, it is required that their plasticity will not be reduced to a dangerous level under radiation damage. However, the plastic deformation capacity of conventional HCP-structured magnesium alloys is limited. Interface engineering is an effective method to improve the radiation resistance of materials. Through interface engineering, high-density grain boundaries, phase boundaries, free crystal planes and other interfaces are introduced into the material as traps for radiation defects, which can effectively regulate the material's resistance to radiation damage and maintain the stability of the material's microstructure and macroscopic properties under strong radiation environments.

[0003] However, the resistance of magnesium alloy grain boundaries, phase boundaries, free crystal planes and other interfaces to radiation has yet to be determined. Dual-phase magnesium-lithium alloys combine the characteristics of the two-phase properties and exhibit extremely high plastic deformation capabilities. The dislocation pile-up and strain concentration at the phase interface have a significant effect on the alloy properties. The resistance of phase boundaries in magnesium-lithium alloys to radiation has also yet to be confirmed. The first-principles calculation method based on density functional theory is a powerful tool for studying material properties at the atomic scale, and can provide effective information for the above-mentioned issues from the physical essence. Therefore, constructing a reasonable calculation model of magnesium alloy grain boundaries / phase boundaries before and after irradiation is crucial to studying the resistance mechanism of magnesium alloys to radiation. Summary of the invention

[0004] In view of the problem of poor plasticity of magnesium alloy after irradiation in the prior art and the unclear mechanism of grain boundary and phase boundary resistance to irradiation of magnesium alloy, the present invention provides a method for constructing and evaluating an alloy phase boundary / grain boundary irradiation damage behavior model, comprising the following steps:

[0005] S1: According to the EBSD results of AZ31, the crystal plane and crystal plane angle of α-Mg in AZ31 are obtained. According to the TEM results of LZ91, two crystal planes are obtained, namely and (200) Li Crystal planes and crystal plane angles, constructing the phase boundary interface model of α-Mg and β-Li;

[0006] S2: Based on the crystal plane and orientation information obtained in S1, a surface model is constructed, and the supercell models of α-Mg with face-centered cubic structure and β-Li with body-centered cubic structure are constructed respectively. The (200) crystal plane cuts the α-Mg and β-Li supercell models to obtain a two-phase supercell plate model containing a surface. Then the number of atomic layers of the surface model is determined, and a vacuum isolation layer is added above the surface model. The surface model is tested for convergence, and the results are obtained from (0002) Mg The interface model of AZ31 magnesium alloy composed of crystal planes, and and (200) Li LZ91 magnesium-lithium alloy interface model composed of crystal planes;

[0007] S3: By doping a Mg vacancy, a Li vacancy, or a Mg vacancy and a Li vacancy into the interface model obtained in S2, a model of alloy phase boundary / grain boundary radiation damage behavior was constructed.

[0008] Furthermore, the angle of the crystal plane of α-Mg described in S1 is 7.8°, and the crystal plane of α-Mg is (0002) Mg .

[0009] Furthermore, as described in S1 and (200) Li The angle between the crystal planes is 1°.

[0010] Furthermore, the thickness of the vacuum isolation layer described in S2 is

[0011] The convergence test described in S2 is further used to determine whether the surface model has converged by using the surface energy of the surface model with different numbers of layers. The surface energy is calculated as follows:

[0012]

[0013] Where A represents the surface area; N bulk and N slab are the number of atoms in the bulk structure and the surface structure, respectively; is the total energy of the atom in the bulk structure; E tot is the total energy of the surface; E suf (N) is the surface energy of the relevant surface model obtained after calculation.

[0014] Furthermore, the interface model of the AZ31 magnesium alloy described in S2 is (0002) Mg / (0002) Mg Grain boundaries, by placing 5 layers (0002) Mg Placed on 5th floor (0002) MgAbove, then the 5th layer above (0002) Mg Rotate 7.8° to get.

[0015] Furthermore, the interface model of the LZ91 magnesium-lithium alloy described in S2 is and (200) Li By placing 6 layers (200) Li Place on 3rd floor Above, then the upper 6 layers (200) Li Rotate 1° to get.

[0016] An evaluation method for an alloy phase boundary / grain boundary radiation damage behavior model comprises the following steps: calculating the interface energy and adhesion work before and after irradiation through the alloy phase boundary / grain boundary radiation damage behavior model, and judging the stability of the interface after irradiation through the difference;

[0017] By comparing the electronic properties of AZ31 grain boundaries and LZ91 phase boundaries, the effect of irradiation-induced vacancies on the interface stability of AZ31 grain boundaries and LZ91 phase boundaries was obtained.

[0018] Furthermore, the interface properties include interface energy and interface theoretical strength (adhesion work), and the electronic properties include state density, differential charge density and Bader charge.

[0019] Beneficial Effects

[0020] (1) Through the construction method and evaluation method of the alloy phase boundary / grain boundary irradiation damage behavior model provided by the present invention, in the geometric optimization, the control variable method is used to check its energy convergence, so as to obtain a balanced and stable crystal structure, and by constructing the interface model of the grain boundary and conducting the structural convergence test of the surface model, the appropriate number of atomic layers is obtained, and by conducting the convergence test of the surface model, the calculation cost is reduced and the calculation accuracy is improved, and a surface model is added above each surface model. The vacuum layer of thickness is used to prevent the interaction between the surfaces. The effect of vacancies on the interface properties is obtained by first principle, and the damage effect of Au ion irradiation on the phase boundary of magnesium alloy is explored by doping one Mg vacancy, one Li vacancy, one Mg vacancy and Li vacancy separately.

[0021] (2) The present invention constructs a primary irradiation interface model for first-principles calculations, which has been successfully applied to the computational study of AZ31 grain boundary and LZ91 phase boundary irradiation damage behavior. The data obtained from the observation experiment (EBSD, TEM) are used to obtain information such as the crystal planes and their angles that constitute the interface. The construction of the interface model can be used to study the more specific simulation of the damage behavior of irradiation on the real interface. The model uses a Mg vacancy, a Li vacancy, a Mg vacancy and a Li vacancy to explore the damage effect of Au ion irradiation on the magnesium alloy phase boundary, and realizes the effective simulation of the interface properties when containing different types of primary irradiation defect vacancies. It has the remarkable characteristics of low computational cost and accurate calculation results. The present invention also provides a method for calculating and studying the influence of radiation on the degree of interface damage. By calculating the interface energy, interface theoretical strength (adhesion work) and Bader charge change at the interface of AZ31 grain boundary and LZ91 phase boundary before and after irradiation, the difference between the three is obtained. Not only the strength of the resistance of grain boundary and phase boundary to radiation is analyzed, but also the influence of different types of vacancy radiation defects on the interface properties and electronic properties of phase boundary is determined, which provides reliable and effective physical information at the atomic scale for revealing the degree of damage of primary radiation defects to the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0023] Figure 1 is a surface model diagram in the convergence test of the present invention;

[0024] Figure 2 Surface energy diagrams of surfaces of different atomic layers of the present invention;

[0025] Figure 3 The interface model diagram of LZ91 and AZ31 of the present invention;

[0026] Figure 4 The difference diagram of interface energy and interface theoretical strength of AZ31 and LZ91 of the present invention;

[0027] Figure 5 The total density of states (DOS) and partial density of states (PDOS) diagrams of AZ31 of the present invention;

[0028] Figure 6 is the differential charge density diagram of AZ31 of the present invention;

[0029] Figure 7is the differential charge density diagram of the 001 surface of the present invention;

[0030] Figure 8 is the Bader charge diagram of AZ31 of the present invention;

[0031] Fig. 9 The total density of states (DOS) and partial-wave density of states (PDOS) diagram of LZ91 of the present invention;

[0032] Fig.10 is the differential charge density diagram of LZ91 of the present invention;

[0033] Fig.11 is the differential charge density diagram of the 010 surface of the present invention;

[0034] Fig.12 It is the Bader diagram of LZ91 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with Example 1 of the present invention and the attached Figures 1 to 12 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The present invention mainly uses the DS-PAW module of the multi-scale material design and simulation platform Device Studio software. Based on the ground state solution of autonomous calculation, various electronic structure properties of the system can be obtained, such as state density, electron local density, partial charge (pcharge), Bader charge analysis, state density, partial wave state density, etc.

[0037] First, in order to obtain the ground state energy of a single atom, the geometry of the unit cell must be optimized to ensure that the subsequent parameter selection is reliable; in the geometry optimization, the method of controlling variables is used to verify its energy convergence, so as to obtain a balanced and stable crystal structure. For the selection of cutoff energy, 400eV is selected according to the reference, and the K point value is automatically selected by the DS-PAW system according to different crystal structures; under the above parameters, the ground state energies of Mg and Li atoms are -24.655eV and -204.67eV respectively;

[0038] In order to construct the interface model of the grain boundary, the EBSD result map of AZ31 obtained by the experiment was analyzed to obtain the crystal plane angle of α-Mg in AZ31. The two crystal planes with the smallest angle, namely the (0002) with an angle of 7.8°, were selected. MgSimilarly, to construct the phase boundary model of α-Mg and β-Li, the TEM results of LZ91 were analyzed and the two crystal planes with the smallest angle were obtained as and (200) Li , the minimum angle is 1°; in order to improve the calculation accuracy, the present invention obtains the result of the surface model convergence test by testing the structural convergence of the surface model, and selects the one with the least number of layers among multiple numbers of layers within the acceptable error range; then, the surface model of the corresponding number of layers is stacked and spliced ​​according to the crystal plane orientation relationship and crystal plane angle information obtained by S1, and a vacuum layer is added along the

[001] direction above one side of the surface, and the (0002) and (0001) layers with two angles of 7.8° are obtained. Mg The interface model of AZ31 magnesium alloy composed of crystal planes and the angle of 1° Mg and (200) Li LZ91 magnesium-lithium alloy interface model composed of crystal planes.

[0039] Example 1

[0040] A method for constructing an alloy phase boundary / grain boundary radiation damage behavior model comprises the following steps;

[0041] S1: First, obtain the EBSD result image of the single-phase magnesium alloy AZ31 and the TEM structure image of the dual-phase magnesium-lithium alloy LZ91, and then select the crystal plane with the smallest angle according to the crystal plane orientation information in the image. For the AZ31 magnesium alloy, select the (0002) with two angles of 7.8°. Mg The crystal plane is used to obtain the grain boundary of the magnesium alloy, and for LZ91 magnesium-lithium alloy, the angle of 1° is selected. and (200) Li Crystal planes to obtain phase boundaries of magnesium alloys;

[0042] S2: Determine the number of atomic layers on each crystal plane and construct a magnesium alloy grain boundary / phase boundary interface model, and add The vacuum layer of thickness is used to prevent the interaction between the surfaces. The surface model is constructed through the crystal plane obtained by S1, and then the surface model is tested for convergence. The surface energy of the surface models with different numbers of layers is used to measure whether convergence is achieved. The specific expression formula for surface energy calculation is as follows:

[0043]

[0044] Where A represents the surface area; N bulk and N slab are the number of atoms in the bulk structure and the surface structure, respectively; is the total energy of the atom in the bulk structure; E tot is the total energy of the surface; E suf(N) is the surface energy of the relevant surface model obtained after calculation;

[0045] Combination Figure 1 The convergence test process can be used to obtain the different atomic layers. and (200) Li Surface model, combined Figure 2 The convergence test process can be used to obtain the different atomic layers. and (200) Li The surface energy of the surface, Figure 2 The surface energy results of different surface models are used to obtain the number of atomic layers suitable for different surface models; 3 layers and 6 floors (200) Li ; For (0002) Mg The surface model thickness is selected as 5 atomic layers;

[0046] By obtaining the results of the surface model convergence test, the 5 layers (0002) Mg Placed on 5th floor (0002) Mg Above, then the 5th layer above (0002) Mg Rotate 7.8° to get (0002) Mg / (0002) Mg Grain boundaries, by placing 6 layers (200) Li Place on 3rd floor Above, then the upper 6 layers (200) Li Rotate 1° and you get Phase boundary, from the surface model, we know that (200) Li The lattice constants of the surface are The lattice constants of the surface are (0002) Mg The lattice constants of the surface are therefore The mismatch degree of the phase boundary is 10.6%; according to the two-dimensional lattice mismatch theoretical model proposed by Bremfitt et al., (0002) Mg / (0002) Mg Grain boundaries and The effect of the mismatch of the phase boundary on the calculation results can be ignored. Considering the periodic boundary conditions, the coherence between the interfaces is achieved by slightly stretching or compressing Mg in the U and V directions, which compensates for the mismatch of the interfaces. On this basis, by adding The vacuum isolation layer effectively avoids the interaction between interfaces;

[0047] S3: The first principles are used to explore the effect of vacancies in primary radiation damage on interface properties; therefore, on the basis of the initial LZ91 phase boundary, a Mg vacancy, a Li vacancy, a Mg vacancy and a Li vacancy are doped respectively, and according to the type of doped vacancies, the alloy phase boundary / grain boundary radiation damage behavior model is constructed, which is named LZ91-Mg, LZ91-Li and LZ91-Mg-Li, respectively, to explore the effect of Au ion irradiation on the phase boundary of magnesium alloy; similarly, on the basis of the initial AZ31 grain boundary, a Mg vacancy is doped and named AZ31-Mg, to explore the effect of Au ion irradiation on the grain boundary of magnesium alloy, such as Figure 3 As shown, Figure 3 (a) is LZ91, Figure 3 (b) is LZ91-Mg, Figure 3 (e) is LZ91-Li, Figure 3 (d) is LZ91-Mg-Li, Figure 3 (e) AZ31, Figure 3 (f) is AZ31-Mg.

[0048] An evaluation method for an alloy phase boundary / grain boundary radiation damage behavior model comprises the following steps:

[0049] First, the interface characteristics of the grain boundary and the phase boundary are characterized by the interface energy and interface theoretical strength (adhesion work); the interface energy γ AB It is an important thermodynamic parameter in metal materials. It reflects the increase in free energy caused by the disordered arrangement of atoms in the system. The calculation formula can be expressed as:

[0050]

[0051] Among them, A interface represents the interface area, It is the total energy of the interface; and are the surface energies of different surfaces; N i is the number of i atoms in the interface model, is the chemical potential of i atoms in the corresponding surface model, and is numerically equal to the energy of a single i atom because the surface model selected by the convergence test has the characteristics of the bulk structure model;

[0052] Adhesion work W ad It reflects the theoretical strength of the interface between the precipitate phase and the matrix. The higher the value, the stronger the interaction between atoms on both sides of the interface. The specific calculation formula is as follows:

[0053]

[0054] In the formula, and represent the total surface model energy of A and B respectively; E AB is the interfacial energy; A interface is the interfacial area;

[0055] The interfacial energy and adhesion work of AZ31 grain boundary and LZ91 phase boundary are calculated respectively, and combined with Figure 4 It can be seen that the difference between the interface energy and adhesion work before and after irradiation can be obtained by comparing the interface energy and adhesion work before and after irradiation. The larger the difference, the worse the interface stability after irradiation and the worse the resistance to radiation.

[0056] In order to further analyze the effect of vacancies induced by radiation on the interface properties of AZ31 grain boundaries and LZ91 phase boundaries, the differences in electronic properties such as state density, differential charge density and Bader charge of the interface models before and after irradiation were compared. The effect of irradiation on the stability of AZ31 grain boundaries and LZ91 phase boundaries was obtained by comparing the state density and differential charge density, and the degree of influence of irradiation on the interface properties was measured by calculating the change in Bader charge.

[0057] Figure 4 The calculation results of the interface energy and adhesion work of AZ31 and LZ91 show that the changes in the interface energy and adhesion work of AZ31 before and after irradiation are generally smaller than those of LZ91, and the interface stability of AZ31 is less affected after irradiation, which shows that the resistance of AZ31 grain boundary to irradiation is stronger than that of LZ91 phase boundary. In addition, in LZ91, the influence of Li vacancy doping on the interface properties and resistance to irradiation damage of LZ91 phase boundary is greater than that of Mg vacancy doping.

[0058] As one of the most important characterizations of electronic structure, the bonding state and interaction state in the electronic structure have an important influence on the stability of the material. Figure 5 (ab) are the total density of states (DOS) and atomic partial density of states (PDOS) curves of AZ31 and AZ31-Mg, respectively. The blue dashed line represents the Fermi level. The valence electrons of each element in the AZ31 grain boundary are: Mg2p 6 3s 2 ;

[0059] Depend on Figure 5It can be seen that the bonding electrons of AZ31 are mainly distributed in the range of -7.5 to 3.3 eV. In the range of -7.5 to -1.6 eV, the bonding electrons of AZ31 are mainly contributed by the s electrons of Mg; in the range of -1.6 to 3.3 eV, the bonding electrons of AZ31 are mainly contributed by the p electrons of Mg; in the range of -7.5 to 3.3 eV, the s and p electronic states of Mg atoms show obvious hybridization, indicating the formation of Mg-Mg metallic bonds. The bonding electron distribution of AZ31-Mg is similar to that of the initial AZ31 grain boundary, except that the hybridization area of ​​Mg atoms' s electrons and p electrons is reduced by 0.67 after doping with Mg atoms; the more overlapping areas of the valence bands, the stronger the hybridization effect and the more stable the interface, indicating that the stability of the AZ31 grain boundary is weakened after doping with Mg vacancies; the electronic state density corresponding to the Fermi level of the initial AZ31 is 2.85eV, and the electronic state density corresponding to the Fermi level of AZ31-Mg is 2.73eV, which is a decrease of 0.12eV; the higher the electronic state density corresponding to the Fermi level, the more unstable the system is, but the electronic state density at the Fermi level of AZ31 before and after doping with vacancies changes slightly and can be ignored; in general, after doping with vacancies, the stability of the AZ31 interface decreases, but the change is not significant;

[0060] Then the differential charge density and Bader charge of AZ31 are calculated; the differential charge density defines the redistribution of charge in the system after the atoms are arranged into a crystal, which can directly show the charge distribution and bonding ability; the initial AZ31 differential charge density is as follows Figure 6 As shown, we can get the part where we lose electrons and gain electrons, and the value of the isosurface is from Figure 6 It can be found that in the initial AZ31 model, for most Mg atoms, the electrons are approximately uniformly distributed around them, while the gap density between adjacent Mg atoms is slightly higher, showing typical metallic bond characteristics; for the grain boundary part in the AZ31 model, the electrons are initially distributed around isolated Mg atoms. Once another surface Mg atom is adsorbed to (0002) Mg Surface, (0002) Mg The atoms on the surface will transfer between them; it is worth noting that the charge transfer mainly occurs on the two-layer surface, while the charge density of the internal atoms does not change much, indicating that the adsorption of Mg atoms only affects the two-layer surface atoms; similarly, for the AZ31-Mg model, after doping vacancies (0002) Mg As the number of Mg atoms adsorbed on the surface decreases, the amount of charge transfer also decreases, resulting in a new surface structure; the more charge transfer there is, the stronger the bonding ability of the atoms. This shows that the surface stability of AZ31 is weakened after doping with vacancies.

[0061] In order to observe the differential charge density more intuitively, the present invention intercepted the (001) surface of the initial AZ31 and AZ31-Mg respectively, and the results are as follows: Figure 7 The contour lines of the initial AZ31 and AZ31-Mg surfaces are selected as arrive and arrive The results show that the results of the two-dimensional differential charge diagram of AZ31 and AZ31-Mg are Figure 6 The results are consistent.

[0062] In addition, in order to quantify the charge transfer, this chapter calculates the Bader charge of AZ31. The calculation results are shown in Figure 8 Layer 5-6 of the 10 layers of Mg atoms in AZ31 is at the grain boundary interface. The Bader charge differences of layer 5 and layer 6 of AZ31 and AZ31-Mg are 0.473e and 0.466e, respectively, which decreases by 0.007e after doping with vacancies, indicating that the charge transfer of AZ31 is more intense, which is consistent with the conclusion of the differential charge density.

[0063] Similarly, the electronic properties of LZ91 before and after irradiation are calculated to analyze the charge transfer at the phase boundary and the interface stability. Fig. 9 (ad) are the total density of states (DOS) and atomic partial density of states (PDOS) curves of LZ91, LZ91-Mg, LZ91-Li, and LZ91-Mg-Li, respectively. The blue dashed line represents the Fermi level. The valence electrons of each element in the LZ91 phase boundary are: Mg2p 6 3s 2 and Li1s 2 2s 1 .

[0064] Depend on Fig. 9 It is known that the bonding electrons of LZ91 are mainly distributed in the range of -10 to 2eV. In the range of -10 to -7.5eV, the bonding electrons of LZ91 are mainly contributed by the s electrons of Mg. In the range of -7.5 to 2eV, the s and p electron states of Mg and Li atoms show obvious hybridization, indicating that Mg and Li have bonding interactions, and the contribution of Mg atoms to the valence band is greater than that of Li atoms. Similarly, the bonding electrons of LZ91-Mg, LZ91-Li, LZ91-Mg-Li and LZ91 in the range of -10 to -7.5eV are mainly contributed by the s electrons of Mg, indicating the formation of Mg-Li ionic bonds. In the range of -7.5 to -4eV, the bonding electrons have no contribution from Li atoms, only the contribution from the s and p electrons of Mg, and the hybridization area of ​​Mg and Li atoms is significantly reduced, indicating that the Mg-Li ionic bonds of LZ91 are greatly reduced after doping with vacancies.

[0065] In addition, the overlap areas of LZ91-Li and LZ91-Mg-Li are the same, and both are larger than the overlap area of ​​LZ91-Mg. This shows that after doping with Mg and Li vacancies, the stability of the system is weakened, and the effect of doping with Li vacancies on the stability of LZ91 is greater than that of doping with Mg vacancies. In the range of -4 to 2 eV, the s and p electronic states of Mg atoms and the s and p electronic states of Li atoms in the three interface models doped with vacancies show obvious hybridization, among which the overlap areas of the three phase boundaries doped with vacancies are the same in the range of -4 to 0 eV. Secondly, the electronic state density corresponding to the initial LZ91 phase boundary Fermi level is 6.044eV. Through the doping of Mg vacancies and Li vacancies, the Fermi surface moves toward the high energy level region, thereby increasing the state density of the corresponding Fermi surface. The state density corresponding to the Fermi level of LZ91-Mg, LZ91-Li and LZ91-Mg-Li is 6.296eV, 6.656eV, and 6.381eV, respectively. The increase in the electronic state density relative to the initial LZ91 phase boundary is 0.252eV, 0.337eV, and 0.612eV, respectively. Among them, the largest increase in electronic state density is LZ91-Li, which is twice that of the other two phase boundaries. This shows that after doping with Mg and Li vacancies, the stability of the system is weakened, and the effect of doping with Li vacancies on the stability of the system is greater than that of doping with Mg vacancies.

[0066] The differential charge density results of LZ91 are as follows Fig.10 As shown, Fig.10 (ab) The isosurface is Fig.10 (cd) isosurface Fig.10 (a) It can be found that in the initial LZ91 phase boundary, obvious charge transfer occurs around each Mg and Li atom, and the charge transfer amount of Li is greater than that of Mg, indicating that Mg atoms and Li atoms will affect each other's internal charge density and the influence of Li atoms is stronger than that of Mg atoms. There is also obvious charge transfer at the initial LZ91 phase interface, indicating that a Mg-Li bond is formed at the phase boundary. It can be seen that the electron cloud around Mg atoms is mainly blue, while the electron cloud around Li atoms is yellow, indicating that at the phase boundary interface, it is mainly Mg atoms that lose electrons and Li atoms that gain electrons. In addition, there is also a small amount of charge distribution in the vacuum layer. Similarly, the differential charge density of LZ91-Mg is as follows Fig.10 As shown in (b), the amount of partial charge transfer of the Mg vacancy doped at the interface is significantly reduced, while the amount of charge transfer of the surrounding atoms is increased. In addition, the charge density inside the Li atom has also changed significantly. The Li atoms in the third layer (002) Li have lost more charge, while the Li atoms in the sixth layer have lost less charge, and the charge distribution in the vacuum layer is almost 0. This shows that after doping with Mg vacancies, the stability of LZ91 is weakened.

[0067] The differential charge density of LZ91-Li is as follows Fig.10 As shown in (c), the change in overall charge density is very obvious. After doping a Li vacancy, the differential charge inside the Mg and Li atoms in the interface model disappears, indicating that in the LZ91-Li interface model, the charge distribution around the Mg and Li atoms is uniform and no obvious charge transfer occurs. When (1100) Mg and (200) Li After adsorbing Li atoms and Mg atoms, the charge at the phase boundary is transferred to form a Mg-Li bond. The differential charge density of LZ91-Mg-Li is shown in Fig.10 As shown in (d), its charge distribution is very similar to that of LZ91-Li, except that the charge transfer amount is reduced at the Mg vacancy doped site.

[0068] The (010) surfaces of the four models of LZ91 were cut off and analyzed respectively. The results are as follows: Fig.11 In order to visually observe the effect of the differential charge density diagram, the contour lines of LZ91, LZ91-Mg, LZ91-Li, and LZ91-Mg-Li are selected arrive arrive arrive and arrive As shown in the figure, the charge distribution in the LZ91 phase boundary is greatly affected by the doping of Li vacancies, and the charge transfer amount is reduced at the doping of Mg vacancies.

[0069] Fig.12 is the average Bader charge distribution of atoms in each layer of the four LZ91 models, where layer (1-6) is (200) Li , layer(7-9) is Layer 6-7 is LZ91 (200) Li and The contact position. Fig.12 (a) It can be seen that the Bader charge of the initial LZ91 decreases sharply at layer 6-7, (200) Li The Bader charge is 3.115e, The Bader charge of LZ91-Mg is 1.919e, which means that the Li atom gains electrons while the Mg atom loses electrons in LZ91, and the Bader charge difference between the two is 1.196e. The Bader charge of LZ91-Mg is not much different from the initial LZ91 phase boundary. In layer (1-6) and layer (7-9), that is, inside the Li atoms and Mg atoms, the trends of Bader charge changes are basically the same, with slight differences in values, indicating that the charge distribution of the two is similar. In addition, inside the Mg atoms, the Bader charge curve shows a slow upward trend, indicating that the electrons around the Mg atoms are gradually transferred from the phase boundary to the inside of the Mg atoms, which is consistent with the conclusion of differential charge. It is worth noting that in layer 7, that is, the atomic layer doped with Mg vacancies, the Bader charge is significantly reduced. In layer 6-7, its (200) Li and The Bader charges of the phase boundaries are 3.260e and 1.632e, respectively, with a difference of 1.62e. The amount of charge transfer increases at the phase boundary, indicating that the stability of the phase interface is improved after doping with Mg vacancies at the phase boundary.

[0070] For LZ91-Li and LZ91-Mg-Li, the change trend of the Bader charge of the two is quite different from that of the initial LZ91. In layer (1-6), that is, the Bader charge inside the Li atoms of LZ91-Li fluctuates greatly, indicating that after doping with Li, the charge at the phase boundary is significantly transferred. In layer (7-9), that is, inside the Mg atoms, the Bader charge shows a downward trend, indicating that the charge around the Mg atoms gradually transfers from the inside of the Mg atoms to the phase boundary, which is opposite to the trend inside the Mg atoms of the initial LZ91. In layer 7, that is, the atomic layer doped with Li vacancies, the Bader charge is significantly reduced. The (200) of layer 6 and 7 Li and The Bader charges of LZ91-Mg-Li are 2.859e and 2.197e, respectively, with a difference of 0.662e. The amount of charge transfer at the phase boundary is reduced, indicating that after doping with Li vacancies at the phase boundary, the interface stability at the phase boundary is weakened. For LZ91-Mg-Li, charge transfer occurs in the atomic layers of Li and Mg atoms close to the interface. Unlike LZ91-Li, the Bader charge fluctuation of Mg atoms is more drastic than that of Li atoms. It is worth noting that the Bader charge of layer 7 doped with Mg vacancies is significantly increased, indicating that a large amount of charge is transferred here. In layer 6-7, its (200) Li and The Bader charges are 2.937e and 2.619e, respectively, with a difference of 0.316e. The amount of charge transfer at the phase boundary is reduced, indicating that at the phase boundary, compared with the initial LZ91 phase interface, the interface stability at the phase boundary is weakened after doping Mg vacancies and Li vacancies; compared with the interface doped with Li vacancies, the stability at the phase boundary is weakened again after doping one more Mg vacancy.

Claims

1. A method for constructing an alloy phase boundary / grain boundary radiation damage behavior model, characterized in that: The following steps are involved: S1: According to the EBSD results of AZ31, the crystal plane and crystal plane angle of α-Mg in AZ31 are obtained. According to the TEM results of LZ91, two crystal planes are obtained, namely and (200) Li Crystal planes and crystal plane angles, constructing the phase boundary interface model of α-Mg and β-Li; S2: Based on the crystal plane and orientation information obtained in S1, a surface model is constructed, and the supercell models of α-Mg with face-centered cubic structure and β-Li with body-centered cubic structure are constructed respectively. The (200) crystal plane cuts the α-Mg and β-Li supercell models to obtain a two-phase supercell plate model containing a surface. Then the number of atomic layers of the surface model is determined, and a vacuum isolation layer is added above the surface model. The surface model is tested for convergence, and the results are obtained from (0002) Mg The interface model of AZ31 magnesium alloy composed of crystal planes, and and (200) Li LZ91 magnesium-lithium alloy interface model composed of crystal planes; S3: By doping a Mg vacancy, a Li vacancy, or a Mg vacancy and a Li vacancy into the interface model obtained in S2, a model of alloy phase boundary / grain boundary radiation damage behavior was constructed.

2. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: The angle of the α-Mg crystal plane described in S1 is 7.8°, and the α-Mg crystal plane is (0002) Mg .

3. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: As described in S1 and (200) Li The angle between the crystal planes is 1°.

4. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: The thickness of the vacuum insulation layer described in S2 is 5. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: The convergence test described in S2 determines whether the surface energy of the surface model with different numbers of layers is converged. The surface energy is calculated as follows: Where A represents the surface area; N bulk and N slab are the number of atoms in the bulk structure and the surface structure, respectively; is the total energy of the atom in the bulk structure; E tot is the total energy of the surface; E suf (N) is the surface energy of the relevant surface model obtained after calculation.

6. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: The interface model of AZ31 magnesium alloy described in S2 is (0002) Mg / (0002) Mg Grain boundaries, by placing 5 layers (0002) Mg Placed on 5th floor (0002) Mg Above, then the 5th layer above (0002) Mg Rotate 7.8° to get.

7. The method for constructing an alloy phase boundary / grain boundary radiation damage behavior model according to claim 1, characterized in that: The interface model of LZ91 magnesium-lithium alloy described in S2 is and (200) Li By placing 6 layers (200) Li Place on 3rd floor Above, then the upper 6 layers (200) Li Rotate 1° to get.

8. A method for evaluating an alloy phase boundary / grain boundary radiation damage behavior model, characterized in that: The following steps are involved: Through the alloy phase boundary / grain boundary radiation damage behavior model, the interface energy and adhesion work before and after irradiation are calculated, and the stability of the interface after irradiation is judged by the difference; By comparing the electronic properties of AZ31 grain boundaries and LZ91 phase boundaries, the influence of irradiation-induced vacancies on the interface properties of AZ31 phase boundaries and LZ91 grain boundaries was obtained.

9. The method for evaluating the alloy phase boundary / grain boundary radiation damage behavior model according to claim 8, characterized in that: The interface properties include interface energy and interface theoretical strength (adhesion work), and the electronic properties include state density, differential charge density and Bader charge.

Citation Information

Patent Citations

  • High-room-temperature ductility magnesium alloy material and preparation method thereof

    CN102925771A

  • Preparation method of high-strength Mg-Gd-Zn-Li magnesium alloy for engineering structural member

    CN114032406A

  • Method for evaluating interface bonding strength based on first principle

    CN115206465A

  • Novel rare earth hard alloy theoretical calculation and analysis

    CN115312140A

  • Irradiation hardening analysis method of nano nickel-molybdenum-chromium alloy under ion irradiation condition

    CN116312893A

Cited By

  • High-throughput calculation method for predicting performance of tungsten-molybdenum alloy connection interface

    CN119626417A